PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS BENIME TEMA PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP PADA SISWA KELAS III SDN 101893 BANGUN REJO - Chairiyah Chairiyah (Universitas Negeri Medan, 2021)
Abstract : Pengembangan Media Pembelajaran Video Animasi Tema Pertumbuhan dan Perkembangan Makhluk Hidup Pada Siswa Kelas III SDN 101893 Bangun Rejo. This study aims to develop a Benime-based animated video learning media on the theme of growth and development of living things in third grade elementary school students that is feasible to use and according to student needs. This type of research is a development that refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). However, this research is limited to the third stage, namely the development stage. This research was conducted at SDN 101893 Bangun Rejo. The instrument used in this study was a questionnaire validation sheet. The subjects in this study were 3 validators including 1 expert lecturer and 2 elementary school teachers. The types of data in this study are qualitative and quantitative data. The results of the validation of media experts and material experts from this study are as follows, based on the results of the validation of the Benime- based animated video learning media experts from the validator, it shows a total average of 82.8% and the results of the material expert validators from the 2 validators show a total average of 82% with Thus the Benime-based animated video learning media shows the